Cultural concepts of distress and complex PTSD: Future directions for research and treatment. (April 2022) - Heim, Eva; Karatzias, Thanos; Maercker, Andreas
Abstract: Complex post-traumatic stress disorder (CPTSD) was introduced as a new diagnostic category in ICD-11. It encompasses PTSD symptoms along with disturbances in self-organisation (DSO), i.e., affect dysregulation, negative self-concept, and disturbances in relationships. Quantitative research supports the validity of CPTSD across different cultural groups. At the same time, evidence reveals cultural variation in the phenomenology of PTSD, which most likely translates into cultural variation with regard to DSO. This theoretical review aims to set the ground for future research on such cultural aspects in the DSO. It provides a theoretical introduction to cultural clinical psychology, followed by a summary of evidence on cultural research related to PTSD and DSO. This evidence suggests that the way how DSO symptoms manifest, and the underlying etiological processes, are closely intertwined with cultural notions of the self, emotions, and interpersonal relationships and interpersonal relationships. We propose directions for future research and implications for culturally sensitive clinical practice. Highlights: Complex Post-Traumatic Stress Disorder (C-PTSD) is a new diagnosis in ICD-11. C-PTSD captures universal features of human reactions to severe trauma. C-PTSD includes symptoms of PTSD along with disturbances in self-organization (DSO). Evidence reveals cultural variation regarding the DSO, but more research is needed.